Research Data Processing Training for Teachers of SMP Negeri 3 Parepare: Pelatihan Pengolahan Data Penelitian Bagi Guru-Guru SMP Negeri 3 Parepare - Lince, Ranak; Husnaeni, Husnaeni; Rustam, Rustam; Kartini, Kartini; Halim, Patmawati (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
Community Service activities were carried out in Parepare City, Bacukiki District, South Sulawesi Province, precisely at the First High School of Negeri 3 Parepare. The objectives of this activity are to: (1) Increase teachers' knowledge in processing and analyzing research data; (2) Increase awareness and knowledge in teachers about the importance of data management in research data analysis; (3) Increase teachers' insights, abilities, and skills in utilizing data to be more informative with data analysis using excel software; and (4) Reduce the number of teachers who do data processing and analysis intuitively and manually in the computing era. The method used was counseling and teaching, discussion, and training in collaboration between the implementer and the first partner. This method was implemented for all teachers of SMP Negeri 3 Parepare, who were trained for 2 to 4 days and then gradual evaluation and monitoring were carried out periodically for 2 months. The resulting outputs are: (1) increased teacher knowledge in processing and analyzing research data; (2) increased awareness and knowledge of teachers about the importance of processing and analyzing research data; (3) increased teachers' insights, abilities, and skills in utilizing data to be more informative with proper data processing and analysis; and (4) reduced the number of teachers who carry out data processing and analysis intuitively and manually in the computing era, (5) increased competence of trainees in processing research data after training. Abstrak Kegiatan Ipteks bagi Masyarakat dilaksanakan di Kota Parepare Kecamatan Bacukiki, Provinsi Sulawesi Selatan tepatnya di Sekolah Menengah Pertama Negeri 3 Parepare Tujuan kegiatan ini adalah untuk: (1) Meningkatkan pengetahuan guru dalam pengolahan dan menganalisis data penelitian; (2) Meningkatkan kesadaran dan pengetahuan pada guru tentang pentingnya pengelolaan data dalam analisis data penelitian; (3) Meningkatkan wawasan, kemampuan, dan keterampilan guru dalam memanfaatkan data menjadi lebih informatif dengan analisis data menggunakan perangkat lunak excel; dan (4) Mengurangi jumlah guru yang melakukan pengolahan dan analisis data secara intuisi dan manual di era komputasi. Metode yang digunakan adalah penyuluhan dan pengajaran, diskusi, dan pelatihan secara kolaborasi antara pelaksana dengan mitra pertama. Metode ini dilaksanakan kepada semua guru SMP Negeri 3 Parepare, yang dilatih selama 2 s/d 4 hari dan selanjutnya evaluasi bertahap dan monitoring dilakukan secara berkala selama 2 bulan. Luaran yang dihasilkan adalah: (1) pengetahuan guru bertambah dalam pengolahan dan dalam menganalisis data penelitian; (2) Meningkatnya kesadaran dan pengetahuan pada guru tentang pentingnya pengolahan dan analisis data penelitian; (3) Meningkatnya wawasan, kemampuan, dan keterampilan guru dalam memanfaatkan data menjadi lebih informatif dengan pengolahan dan analisis data yang tepat; dan (4) berkurangnya jumlah guru yang melakukan pengolahan dan analisis data secara intuisi dan manual di era komputasi, (5) Bertambahnya kompetensi peserta pelatihan dalam mengolah data penelitian setelah dilaksanakan pelatihan.